Diabetes mellitus, personal autonomy and group practices: an integrative review (Research, Society and Development, 2021)
Objective: identifying evidences of group practices contribution for autonomy of people who live with diabetes mellitus. Method: qualitative integrative review that includes indexed articles in these data bases: Literatura Latino Americana e do Caribe em Ciências da Saúde (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE/PubMed), Scientific Electronic Library Online (SciELO.ORG) and Scopus (Elsevier). We used articles published between 2015 and 2019, in Portuguese and English. The period of collecting data occurred between June and August 2020. Results: we used ten articles with different methodologies performed in different countries. Despite the different approaches and methodologies, all the studies pointed out to some kind of effectiveness for personal autonomy and selfcare acquisition through participation in group intervention. Conclusion: there were several group practices developed to increase autonomy and selfcare on people who have diabetes mellitus and those practices turned out to efficient usage and new interventions were necessary throughout the time. The observance of a professional nurse was reported as essential for the gradual process of those practices acquisition and the usage of active low-cost methodologies, what turns them out to be reproduced in different contexts.